Teachers observing classroom communication: An application of the Communicating Supporting Classroom Observation Tool for children aged 4–7 years. (October 2019) - Law, James; Tulip, Josie; Stringer, Helen; Cockerill, Maria; Dockrell, Julie
The nature of 'Teacher talk' is likely to have a considerable bearing on the child's learning but measuring the communication environment in the classroom can present challenges. One tool which does this is the Communication Supporting Classroom Observation Tool (CSCOT). Initial use suggested that it was valid and reliably used by specialists (psychologists and speech and language therapists) and special educational needs coordinators (SENCOs). A key question is whether it can be used routinely by classroom teachers and whether results coincide with those in earlier studies. CSCOT observations were carried out by teachers in 33 schools (32 Reception classrooms, 25 in Year 1 and 25 in Year 2) in two local authorities in the North East of England and teachers were asked afterwards to reflect on their experiences using the tool. Scores were in line with those in earlier studies and were consistently higher on all dimensions for reception compared to Year 2, but there was no difference between other year groups. Results were mostly consistent with the original studies. Language learning environment was higher relative to both language learning opportunities and interactions across all years (which again did not differ). There was a moderate interaction between language learning environment where scores were significantly higher in the Reception group and lower in the Year 2 group. Teachers supported the use of the CSCOT in their feedback, suggesting that CSCOT was easy to use and useful in informing practice. The CSCOT clearly has utility as a starting point in auditing classroom communication. It allows teachers to compare between classrooms and year groups and potentially fosters collaboration between teachers and specialist practitioners who focus on communication such as speech and language therapists. Further work could link the observation tool into an intervention program co-constructed with teachers.